The Role of Physiognomics in Teaching Students to Draw Portraits - Khudayberdievich, Babadjanov Akhmadjan (Indonesian Journal Publisher, 2024)
In the article, it is true that a teacher of fine arts should have high technical knowledge in drawing portraits in the field of pencil drawing, and also have sufficient knowledge in the field of psychology thought about. This study investigates the role of physiognomics in the instruction of portrait drawing to students. Physiognomics, as the study of facial features and character, has long been believed to be a tool for understanding and capturing human expressions. However, its practical application in teaching portrait drawing has not been fully explored. The research employs a qualitative method, conducting in-depth interviews with art faculty members and experienced art students who are involved in teaching and learning portrait drawing techniques. The findings highlight that the application of physiognomic principles in instruction can assist students in developing a deeper understanding of facial structure and character expression. These findings suggest that integrating physiognomic concepts into the art curriculum can enhance students' portrait drawing skills and enrich their overall artistic experience. This research provides new insights into the importance of incorporating psychological and philosophical aspects into art education, offering a foundation for the development of a more holistic teaching approach in portrait drawing instruction at the higher education level.